Genitalia burn: accident or violence? Concerns that transcend injury treatment - Ana Lúcia Ferreira; Juliana Montez Ferreira; Paula Marques C. da Silva; Dilene Francisco Constancio (Sociedade de Pediatria de São Paulo, 2014)
OBJECTIVE: To describe a case of genital burn which raised the suspicion of maltreatment (sexual abuse and neglect by lack of supervision).CASE DESCRIPTION: An infant was taken to the Emergency Room of a pediatric hospital with an extensive burn in the vulva and perineum. The mother claimed the burn had been caused by a sodium-hydroxide-based product. However, the injury severity led to the suspicion of sexual abuse, which was then ruled out by a multidisciplinary team, based on the consistent report by the mother. Besides, the lesion type matched those caused by the chemical agent involved in the accident and the family context was evaluated and considered adequate. The patient had a favorable outcome and was discharged after four days of hospitalization. Outpatient follow-up during six months after the accident enabled the team to rule out neglect by lack of supervision.COMMENTS: Accidents and violence are frequent causes of physical injuries in children, and the differential diagnosis between them can be a challenge for healthcare workers, especially in rare clinical conditions involving patients who cannot speak for themselves. The involvement of a multidisciplinary trained team helps to have an adequate approach, ensuring child protection and developing a bond with the family; the latter is essential for a continued patient follow-up.